ANALYSIS OF SAR MAIN PARAMETERS FOR SAR SENSOR DESIGN ON LSA - Muchammad Soleh; Rahmat Arief (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2014)
LAPAN plans to conduct a flight test of LSA (LAPAN Surveillance Aircraft). LSA STEMME-S15 is capable of carrying sensor payloads up to 160 kg that are mounted on both sides of the wings with altitude between 400-2000 m. LSA can be designed to perform imaging by using optical sensors and SAR (Synthetic Aperture Radar). Compared to imaging using optical sensors, SAR sensor has advantages such as it can operate all day and night, able to penetrate clouds, and able to see objects from side looking, while optical sensors generally see the object perpendicular to the ground. Therefore the use of SAR imaging technology can complement optical imaging technology. To design SAR system imagers on LSA, it is necessary to simulate the primary parameters SAR i.e. altitude and look angle of sensor, speed of LSA, SAR frequency and signals power shot to object to calculate the resolution of azimuth and ground range values that can be obtained. This SAR parameters simulation used MATLAB which have been designed with two approaches; the first approach where the SAR sensor is ideal and in which all the fundamental parameters (such as polarization, frequency, etc.) are used to generate the desired sensitivity and resolution of azimuth and ground range, and the second approach is where SAR sensor is designed in a limited antenna size (constraint case), with the assumption that the dimensions of the antenna and the average available power are fixed. The data used in this simulation is a pseudo-data obtained from LSA technical spesification and SAR sensor. The simulation results with the first approach shows that if LSA is flying at an altitude of 1000 m, with speed of 36.11 m/s, and SAR frequency of 5.3 GHz, then to get resolution of azimuth, slant range and ground range of 1 m, 1.2 m and 3 m, it is necessary to design the length and width of SAR antenna at 2 m and 13.5 cm, with look angle of 23.5 degrees. While the result of second approach simulation is that if LSA is flying on the same altitude and speed, on the same look angle and SAR frequency, with a particular design of antenna length and width of 2 m and 13.5 cm, then azimuth, slant range and ground range resolution of 1 m, 1.87 and 4.79 m will be obtained. Form both simulations, it can be concluded that limited SAR system on LSA, especially on the technical aspects of mounting and space as in the simulation with the second approach, will produce slightly lower slant range and ground range resolution when compared with SAR system in the first simulation. This shows that space limitation on LSA will affect decrease the value of spatial ground range resolution. The simulation results are expected to be inputs on designing SAR imaging system on LSA.